Tour Guide Training Techniques - Muhammad Syachrun Sjam; Nur Syam (Edumaspul: Jurnal Pendidikan, 2025)
This study provides a comprehensive examination of the techniques and competencies required of professional tour guides to deliver informative, safe, and memorable travel experiences. The discussion focuses on essential skills, including verbal and non-verbal communication, mastery of destination-related knowledge, and the ability to provide excellent service tailored to tourists’ needs and characteristics. The study also highlights the importance of understanding local culture as a foundation for maintaining cultural sensitivity and fostering harmonious interactions between tourists and local communities. In addition, key aspects such as time management, group dynamics management, and emergency handling procedures are identified as crucial elements for ensuring smooth tour operations. The integration of technology—including digital tools and social media—is also examined as a supporting component in information delivery and service enhancement. Emphasis is placed on work ethics, professionalism, and the proactive role of tour guides in maintaining a positive image of the destination. The findings of this study are expected to serve as a reference for developing tour guide competencies and improving service standards within the tourism industry.